Mitochondrial production of reactive oxygen species 2 - Brand, Martin (Henry Stewart Talks, 2018)
Suppressors of electron leaks (SELs), Identification of SELs for various sites, Mitochondrial ROS in signaling and disease, Some biological effects of SELs, Comparisons between SELs, SELs as novel tools to diagnose and modify ROS signaling and damage